SOCIAL LEARNING FOLLOWING ISLAMIC PERSPECTIVES FOR STUDENTS’ MORALE AND PERSONALITY - Daud, Hasbullah Mat; Yussuf, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Education is a critical ingredient in forming high personal morale in students, and it is an imperative asset in Islam. Perfect learning will produce people with high moral values and character. Therefore, several social learning factors influence student morale and personality. This paper aimed to discuss social learning based on Islamic perspectives and social learning factors that can influence students' morale and personality development. Social learning factors can influence and impact students' morale if they can adapt well. This study used the library research methodology by analysing and discussing the content of the text. The data obtained were critically analysed to achieve the objectives of this study. This paper found that social learning factors identified to have a pertinent impression on student morale are parents, peers, schools and teachers, environment and mass media. These factors contributed to social learning and affected the students and played a critical role in influencing a student's personal qualities in shaping excellent personal morale.